Epidemiological and genetic study in 207 cases of oral clefts in Alsace, north-eastern France. Issue 5 (May 1991) - Stoll, C; Alembik, Y; Dott, B; Roth, M P
Abstract : The epidemiology of oral clefts was studied in the geographical area covered by our registry of congenital malformations. For each of the 207 new cases studied during the period 1979 to 1987, more than 50 factors were compared in probands and controls. The incidence of oral clefts was 1.75 per 1000, with cleft lip/palate (CL(P] 0.98 and cleft palate only (CP) 0.77 per 1000. A total of 8.2% of cleft cases were stillbirths and 5.3% were induced abortions. The more common types of associated malformations in the 76 affected cases (36.7%) with at least one anomaly other than oral cleft were neural tube defects and skeletal malformations. At birth, infants with oral clefts and other malformations were smaller, weighed less, and their head circumference was lower than in controls. Placental weight was also lower than in controls. Pregnancies with oral clefts were more often complicated by threatened abortion, polyhydramnios, and arterial hypertension. There was a significant association between clefting and consanguinity; heritability of CL(P) was 81% and first degree relatives of probands had more than three times the prevalence of noncleft malformations as controls. These results are of relevance to genetic counselling.